DESKRIPSI KESADARAN FAKTOR PROTEKTIF DAN FAKTOR RISIKO DALAM PROSES REINTEGRASI SOSIAL PADA NARAPIDANA PEREMPUAN - FX.Wahyu Widiantoro (Jurnal Psikologi, 2016)
Objective of this research is to describe the protective and risk factors in the social reintegration program within a penitentiary. Thirty female convicted criminals were participated in this survey research. At the next several months, they would be released from that penitentiary. They were asked to fill in the Protective and Risk Factor Scale. The scale consists of 15 protective aspect statements 15 risk aspect statements. There were 4 alternative answers for each statement. Validity of those statements was examined through the expert validity, and the reliability score of the scale was .884. Through the descriptive statistics it was revealed that the empirical mean (42.87) was higher than the hypothetic mean (37.5), for the protective factor. For the risk factor, the similar result was found which the empirical mean (40.80) was much higher than the hypothetic mean (37.5). This result showed that those convicted criminals were fully aware that protective factors will support their intention live convenience after being released. On the other hand, they also realize that some factors will obstruct their intention to live happily after being released. At the discussion session, the author suggests to consider the convicted criminal’s culture background. It is because the culture background will color people’s stigma on the exconvicted criminal.